Coating, coating composition, secondary battery, and electronic device

By using a characteristic melamine compound coating in secondary batteries, the problem of poor thermal stability of the existing isolation film at high temperatures is solved, and higher thermal stability and cycling performance are achieved.

CN119315214APending Publication Date: 2025-01-14NINGDE AMPEREX TECHNOLOGY LTD
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202411484011.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

In the existing field of electrochemical energy storage, isolation films made of inactive materials such as alumina, boehmite, barium sulfate, etc. have poor thermal stability and cyclic stability at high temperatures, resulting in poor impedance and storage performance of secondary batteries.

Method used

Using melamine compounds as coating material, by controlling the K1/K2/K3 ratio and particle size distribution in its X-ray diffraction pattern, a sheet-like crystal structure is formed, which improves the thermal shrinkage resistance of the isolation film and reduces the impedance of the secondary battery. Improve high-temperature storage and cycling performance.

Benefits of technology

It effectively reduces the thermal shrinkage degree of the isolation film and the impedance of the secondary battery, improves the high-temperature storage performance and cycling performance, and significantly improves the thermal stability and cycling stability of the secondary battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119315214A_ABST
    Figure CN119315214A_ABST
Patent Text Reader

Abstract

Disclosed are a coating, a coating composition, a secondary battery, and an electronic device, the coating composition including a melamine compound and a binder, the melamine compound including melamine cyanurate, the melamine compound simultaneously satisfying the relational expressions: 1.8 < = K1 / K2 < = 3, 0.18 < = K2 / K3 < = 0.5, and K3 > = K1 > = K2, k1 is the highest peak intensity of the 110 crystal face of the melamine compound, K2 is the peak intensity of the 200 crystal face of the melamine compound, and K3 is the peak intensity of the 202 crystal face of the melamine compound.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of electrochemical energy storage, and in particular to a coating, a coating composition, a secondary battery and an electronic device. Background Art

[0002] In the prior art, aluminum oxide, boehmite, barium sulfate, magnesium oxide, etc. are commonly used as materials to make the coating of the isolation membrane, but these materials are inactive materials and have poor ability to stabilize the battery cell, resulting in poor thermal stability and cycle stability of the battery cell. Summary of the invention

[0003] In view of this, the present application provides a coating, a coating composition, a secondary battery and an electronic device.

[0004] In a first aspect, the present application provides a coating composition, the coating composition comprising a melamine compound, the melamine compound comprising melamine cyanurate, and the melamine compound simultaneously satisfies the following relationship:

[0005] 1.8≤K1 / K2≤3.0,

[0006] 0.18≤K2 / K3≤0.5,

[0007] K3≥K1≥K2,

[0008] Among them, in the X-ray diffraction pattern of the melamine compound, K1 is the highest peak intensity of the melamine compound 110 crystal plane, K2 is the peak intensity of the melamine compound 200 crystal plane, and K3 is the peak intensity of the melamine compound 202 crystal plane.

[0009] The present application controls the relationship between the highest peak intensity K1 of the crystal plane of melamine compound 110, the peak intensity K2 of the crystal plane of melamine compound 200, and the peak intensity K3 of the crystal plane of melamine compound 202, so that the melamine compound has a special crystal plane orientation feature, and the melamine compound is used to make a coating, which can reduce the degree of thermal shrinkage of the isolation membrane at high temperature and reduce the impedance of the secondary battery. When the relationship between K1, K2, and K3 satisfies 1.8≤K1 / K2≤3.0, 0.18≤K2 / K3≤0.5, and K3≥K1≥K2, the morphology of the melamine compound tends to be a lamellar crystal structure, and the melamine compound has a small particle size, a large specific surface area, and a large thermal stability area, which is conducive to improving the heat shrinkage resistance of the isolation membrane or the pole piece and reducing the impedance of the secondary battery, thereby improving the high temperature storage performance, thermal stability, and cycle performance of the secondary battery.

[0010] Based on the first aspect, in some embodiments, the melamine compound satisfies 1.9≤K1 / K2≤2.7. Meeting this condition is conducive to further improving the heat shrinkage resistance of the separator or the pole piece and reducing the impedance of the secondary battery, thereby further improving the high temperature storage performance, thermal stability and cycle performance of the secondary battery.

[0011] Based on the first aspect, in some embodiments, the melamine compound satisfies 0.2≤K2 / K3≤0.5. Meeting this condition is conducive to further improving the heat shrinkage resistance of the separator or the pole piece and reducing the impedance of the secondary battery, thereby further improving the high temperature storage performance, thermal stability and cycle performance of the secondary battery.

[0012] Based on the first aspect, in some embodiments, K1-D is the lowest peak of the crystal plane of the melamine compound 110 in the X-ray diffraction pattern, the peak shape of the K1-D undergoes lattice distortion, the 2θ diffraction angle of the K1-D is at 10.5°±0.5°, the 2θ diffraction angle of the peak corresponding to the K1 is at 10.9°±0.5°, the 2θ diffraction angle of the peak corresponding to the K2 is at 11.8°±0.5°, and the 2θ diffraction angle of the peak corresponding to the K3 is at 28.0°±0.5°.

[0013] Based on the first aspect, in some embodiments, the residual amount of melamine monomer in the melamine compound W1≤1wt%, the residual amount of cyanuric acid monomer in the melamine compound W2≤1wt%, and the residual amount of melamine monomer in the melamine compound W1 and the residual amount of cyanuric acid monomer in the melamine compound W2 are not 0 at the same time. Controlling the residual amounts of melamine monomer and cyanuric acid monomer in the melamine compound within the above range can improve the adhesion of the coating and improve the cycle performance of the secondary battery.

[0014] Based on the first aspect, in some embodiments, the pH of the aqueous solution of the melamine compound is 5≤PH≤6.5, wherein the proportion of water in the aqueous solution of the melamine compound is 90wt%, and the proportion of the melamine compound is 10wt%. Controlling the pH of the aqueous solution of the melamine compound within the above range can improve the adhesion of the coating and improve the cycle performance of the secondary battery.

[0015] Based on the first aspect, in some embodiments, the primary particle size D50 of the melamine compound is 0.3 to 1.5 μm. When the primary particle size D50 of the melamine compound is controlled within this range, it is not easy to cause the melamine compound to block the gaps of the separator, thereby reducing the impedance of the secondary battery, thereby improving the high temperature storage performance, thermal stability and cycle performance of the secondary battery.

[0016] Based on the first aspect, in some embodiments, the primary particle size D50 of the melamine compound is 0.4-1.0 μm. Meeting this condition can further improve the impedance of the secondary battery as well as the high temperature storage performance, thermal stability and cycle performance of the secondary battery.

[0017] Based on the first aspect, in some embodiments, the primary particle size D90 of the melamine compound is 0.6 to 3 μm. The primary particle size D90 of the melamine compound is within this range, so that the thickness of the coating can be controlled within a suitable range and the coating is uniform, thereby reducing the impedance of the secondary battery, thereby improving the high temperature storage performance, thermal stability and cycle performance of the secondary battery.

[0018] Based on the first aspect, in some embodiments, the mass ratio of the melamine compound to the binder is (90-95): (5-10). The mass ratio of the melamine compound to the binder is controlled within this range, which can effectively ensure the adhesion of the coating while reducing the impedance of the secondary battery, thereby improving the thermal stability and cycle performance of the secondary battery.

[0019] A second aspect of the present application provides a coating, comprising the above-mentioned coating composition.

[0020] Based on the second aspect, in some embodiments, the thickness of the coating is 0.8-3.5 μm. The thickness of the coating within this range is beneficial to reducing the impedance of the secondary battery, thereby improving the thermal stability and cycle performance of the secondary battery.

[0021] Based on the second aspect, in some embodiments, the thickness of the coating is 1.0-3 μm. The thickness of the coating within this range is beneficial to further reduce the impedance of the secondary battery, thereby further improving the thermal stability and cycle performance of the secondary battery.

[0022] A third aspect of the present application provides a secondary battery, comprising the above-mentioned coating, a positive electrode plate, a separator and an electrolyte, wherein the coating is disposed on at least one surface of the positive electrode plate or the separator.

[0023] Based on the third aspect, in some embodiments, the electrolyte contains 1,3-propane sultone and fluoroethylene carbonate. The electrolyte containing 1,3-propane sultone and fluoroethylene carbonate can cooperate with the coating to stabilize the anode of the secondary battery, reduce the impedance of the secondary battery, and thus improve the thermal stability and cycle performance of the secondary battery.

[0024] Based on the third aspect, in some embodiments, the sum of the percentages of 1,3-propane sultone and fluoroethylene carbonate in the electrolyte is 0.1% to 5% of the total mass of the electrolyte. Controlling the sum of the percentages of 1,3-propane sultone and fluoroethylene carbonate within this range helps to reduce impedance and improve thermal stability and cycle performance of the secondary battery.

[0025] The fourth aspect of the present application provides an electronic device, comprising the above-mentioned secondary battery. The secondary battery supplies power to the electronic device, and the secondary battery exhibits good thermal stability and cycle performance after high temperature storage performance test, high temperature cycle performance test and hot box test. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is the X-ray diffraction pattern of melamine cyanurate provided in Examples 1-3 of the present application.

[0027] Figure 2 The X-ray diffraction pattern of melamine cyanurate provided for Comparative Examples 1-2 of the present application. DETAILED DESCRIPTION

[0028] The embodiments of the present application are described in detail below. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present application, and cannot be understood as limiting the present application. The reagents and materials in the following embodiments can all be obtained from commercial sources.

[0029] As used in this application, the terms "including," "containing," and "comprising" are used in their open, non-limiting sense.

[0030] In addition, sometimes amounts, ratios and other numerical values ​​are presented in range format herein. It should be understood that such range format is for convenience and brevity, and should be flexibly understood to include not only the numerical values ​​explicitly specified as range limits, but also all individual numerical values ​​or sub-ranges encompassed within the range, as if each numerical value and sub-range were explicitly specified.

[0031] In the detailed description and claims, a list of items connected by the terms "one or more of," "one or more of," "at least one of," or other similar terms may mean any combination of the listed items. For example, if items A and B are listed, the phrase "at least one of A or B" means only A; only B; or A and B. In another example, if items A, B, and C are listed, the phrase "at least one of A, B, or C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may include a single element or multiple elements. Item B may include a single element or multiple elements. Item C may include a single element or multiple elements.

[0032] The present application provides a coating composition, which includes a melamine compound and a binder, wherein the melamine compound includes melamine cyanurate, and the melamine compound satisfies the following relationship at the same time:

[0033] 1.8≤K1 / K2≤3.0,

[0034] 0.18≤K2 / K3≤0.5,

[0035] K3≥K1≥K2,

[0036] Among them, in the X-ray diffraction pattern of the melamine compound, K1 is the highest peak intensity of the melamine compound 110 crystal plane, K2 is the peak intensity of the melamine compound 200 crystal plane, and K3 is the peak intensity of the melamine compound 202 crystal plane.

[0037] The present application controls the relationship between the highest peak intensity K1 of the crystal plane of melamine compound 110, the peak intensity K2 of the crystal plane of melamine compound 200, and the peak intensity K3 of the crystal plane of melamine compound 202, so that the melamine compound has a special crystal plane orientation feature, and the melamine compound is used to make a coating, which can reduce the degree of thermal shrinkage of the isolation membrane at high temperature and reduce the impedance of the secondary battery. When the relationship between K1, K2, and K3 satisfies 1.8≤K1 / K2≤3.0, 0.18≤K2 / K3≤0.5, and K3≥K1≥K2, the morphology of the melamine compound tends to be a lamellar crystal structure, and the melamine compound has a small particle size, a large specific surface area, and a large thermal stability area, which is conducive to improving the heat shrinkage resistance of the isolation membrane or the pole piece and reducing the impedance of the secondary battery, thereby improving the high temperature storage performance, thermal stability, and cycle performance of the secondary battery. If the relationship between K1, K2, and K3 does not satisfy 1.8≤K1 / K2≤3.0, 0.18≤K2 / K3≤0.5, and K3≥K1≥K2, the morphology of the melamine compound will be rod-shaped or irregular granular, and will no longer be a flaky crystal. Using a melamine compound with this morphology to prepare a coating will deteriorate the uniformity of the coating, thereby having a negative impact on the high-temperature storage performance, thermal stability, and cycle performance of the secondary battery.

[0038] In some embodiments, the value of K1 / K2 can be 1.8, 2.0, 2.2, 2.4, 2.6, 2.8, 3.0 or any value within the range formed by any two of the above values. The value of K2 / K3 can be 0.18, 0.20, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5 or any value within the range formed by any two of the above values.

[0039] In some embodiments, the melamine compound satisfies 1.9≤K1 / K2≤2.7, for example, the value of K1 / K2 can be 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7 or any value within the range formed by any two of the above values. Meeting this condition is conducive to further improving the heat shrinkage resistance of the isolation film or the pole piece and reducing the impedance of the secondary battery, thereby further improving the high temperature storage performance, thermal stability and cycle performance of the secondary battery.

[0040] In some embodiments, the melamine compound satisfies 0.2≤K2 / K3≤0.5, for example, the value of K2 / K3 can be 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5 or any value within the range formed by any two of the above values. Meeting this condition is conducive to further improving the heat shrinkage resistance of the isolation film or the pole piece and reducing the impedance of the secondary battery, thereby further improving the high temperature storage performance, thermal stability and cycle performance of the secondary battery.

[0041] Based on the first aspect, in some embodiments, K1-D is the lowest peak of the crystal plane of the melamine compound 110 in the X-ray diffraction pattern, the peak shape of K1-D undergoes lattice distortion, the 2θ diffraction angle of K1-D is at 10.5°±0.5°, the 2θ diffraction angle of the peak corresponding to K1 is at 10.9°±0.5°, the 2θ diffraction angle of the peak corresponding to K2 is at 11.8°±0.5°, and the 2θ diffraction peak of the peak corresponding to K3 is at 28.0°±0.5°.

[0042] In some embodiments, the residual amount of melamine monomer in the melamine compound W1≤1wt%, the residual amount of cyanuric acid monomer in the melamine compound W2≤1wt%, and the residual amount of melamine monomer in the melamine compound W1 and the residual amount of cyanuric acid monomer in the melamine compound W2 are not 0 at the same time. Controlling the residual amounts of melamine monomer and cyanuric acid monomer in the melamine compound within the above range can improve the adhesion of the coating and improve the cycle performance of the secondary battery.

[0043] In some embodiments, the residual amount W1 of melamine monomer in the melamine compound can be 0wt%, 0.1wt%, 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt%, 1wt% or any value within the range formed by any two of the above values, and the residual amount W2 of cyanuric acid monomer in the melamine compound can be 0wt%, 0.1wt%, 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt%, 1wt% or any value within the range formed by any two of the above values, but the residual amount W1 of melamine monomer and the residual amount W2 of cyanuric acid monomer in the melamine compound are not 0 at the same time.

[0044] In some embodiments, the pH of the aqueous solution of the melamine compound is 5≤PH≤6.5, for example, the pH of the aqueous solution of the melamine compound is 5, 5.3, 5.5, 5.8, 6.0, 6.3, 6.5 or any value within the range formed by any two of the above values. Wherein, the proportion of water in the aqueous solution of the melamine compound is 90wt%, and the proportion of the melamine compound is 10wt%. Controlling the pH of the aqueous solution of the melamine compound within the above range can improve the adhesion of the coating and improve the cycle performance of the secondary battery.

[0045] In some embodiments, the primary particle size D50 of the melamine compound is 0.3 to 1.5 μm, for example, the primary particle size D50 of the melamine compound is 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1 μm, 1.1 μm, 1.2 μm, 1.3 μm, 1.4 μm, 1.5 μm or any value within the range formed by any two of the above values. The primary particle size D50 of the melamine compound is controlled within this range, which is not likely to cause the melamine compound to block the pores of the separator or the positive electrode sheet, thereby reducing the impedance of the secondary battery, thereby improving the high temperature storage performance, thermal stability and cycle performance of the secondary battery.

[0046] In the present application, "primary particle size D50" refers to the particle size corresponding to when the cumulative particle size distribution percentage reaches 50% before the particles of the melamine compound agglomerate. The primary particle size D50 of the melamine compound in the aqueous solution is tested using a laser particle size tester.

[0047] In some embodiments, the primary particle size D50 of the melamine compound is 0.4 to 1.0 μm, for example, the primary particle size D50 of the melamine compound is 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1.0 μm or any value within the range formed by any two of the above values. Meeting this condition can further improve the impedance of the secondary battery, thereby improving the high temperature storage performance, thermal stability and cycle stability of the secondary battery.

[0048] In some embodiments, the primary particle size D90 of the melamine compound is 0.6 to 3 μm, for example, the primary particle size D90 of the melamine compound is 0.6 μm, 0.8 μm, 1.0 μm, 1.2 μm, 1.4 μm, 1.6 μm, 1.8 μm, 2 μm, 2.2 μm, 2.4 μm, 2.6 μm, 2.8 μm, 3 μm or any value within the range formed by any two of the above values. The primary particle size D90 of the melamine compound is controlled within this range, so that the thickness of the coating can be controlled within a suitable range and the coating is uniform, reducing the impedance of the secondary battery, thereby improving the high temperature storage performance, thermal stability and cycle performance of the secondary battery.

[0049] In the present application, "primary particle size D90" refers to the particle size corresponding to when the cumulative particle size distribution percentage reaches 90% before the particles of the melamine compound agglomerate. The primary particle size D90 of the melamine compound in the aqueous solution is tested using a laser particle size tester.

[0050] In some embodiments, the mass ratio of the melamine compound to the binder is (90-95): (5-10), for example, the mass ratio of the melamine compound to the binder is 90:10, 91:9, 92:8, 93:7, 94:6, 95:5, or any value within the range formed by any two of the above values. The mass ratio of the melamine compound to the binder is controlled within this range, while effectively ensuring the adhesion of the coating, it can also reduce the impedance of the secondary battery, and play an effect of improving the thermal stability and cycle performance of the secondary battery.

[0051] In some embodiments, the type of binder includes butadiene styrene rubber, polyvinylidene fluoride, vinylidene fluoride-hexafluoropropylene copolymer, styrene-acrylate copolymer, styrene-butadiene copolymer, polyamide, polyacrylonitrile, polystyrene, polyvinyl alcohol, polyethylene glycol, polyacrylate, polyacrylic acid, polyacrylic acid salt, sodium carboxymethyl cellulose, polyvinyl acetate, polyvinylpyrrolidone, polyvinyl ether, polytetrafluoroethylene or polyhexafluoropropylene.

[0052] The present application also provides a coating, comprising the above coating composition. The coating can be formed by coating and drying the coating composition.

[0053] In some embodiments, the thickness of the coating is 0.8-3.5 μm, for example, the thickness of the coating is 0.8 μm, 1.0 μm, 1.2 μm, 1.4 μm, 1.6 μm, 1.8 μm, 2.0 μm, 2.2 μm, 2.4 μm, 2.8 μm, 3.0 μm, 3.2 μm, 3.4 μm, 3.5 μm, or any value within the range formed by any two of the above values. The thickness of the coating within this range is beneficial to reducing the impedance of the secondary battery, thereby improving the thermal stability and cycle performance of the secondary battery.

[0054] In some embodiments, the thickness of the coating is 1.0 to 3.0 μm, for example, the thickness of the coating is 1.0 μm, 1.2 μm, 1.4 μm, 1.6 μm, 1.8 μm, 2.0 μm, 2.2 μm, 2.4 μm, 2.8 μm, 3.0 μm, or any value within the range formed by any two of the above values. The thickness of the coating within this range is beneficial to further reduce the impedance of the secondary battery, thereby further improving the thermal stability and cycle performance of the secondary battery.

[0055] The present application also provides a secondary battery, comprising the above-mentioned coating, a positive electrode plate, a separator and an electrolyte, wherein the coating is arranged on at least one surface of the positive electrode plate or the separator.

[0056] In some embodiments, the positive electrode sheet includes a positive current collector and a positive active material layer disposed on the positive current collector, the positive active material layer may include a positive active material (positive electrode material), and the positive active material layer may be located on one surface of the positive current collector or on two opposite surfaces. In some embodiments, the positive current collector may be made of aluminum foil, and of course, other positive current collectors commonly used in the art may also be used. In some embodiments, the thickness of the positive current collector may be 1 μm to 200 μm. In some embodiments, the positive active material layer may be coated only on a partial area of ​​the positive current collector. In some embodiments, the thickness of the positive active material layer may be 10 μm to 500 μm. It should be understood that these are exemplary only, and other suitable thicknesses may be used.

[0057] In some embodiments, the coating is located on one surface or two opposite surfaces of the positive electrode sheet. In some embodiments, the coating is located on the surface of the positive electrode active material layer away from the positive electrode current collector.

[0058] In some embodiments, the positive electrode active material layer includes a positive electrode active material. In some embodiments, the positive electrode active material may include at least one of lithium cobalt oxide, lithium manganese oxide, lithium iron phosphate, lithium manganese iron phosphate, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, or lithium nickel manganese oxide, and the positive electrode active material may be doped and / or coated.

[0059] In some embodiments, the positive electrode active material layer also includes a positive electrode binder and a positive electrode conductor. In some embodiments, the positive electrode binder may include polyvinylidene fluoride, vinylidene fluoride-hexafluoropropylene copolymer, styrene-acrylate copolymer, styrene-butadiene copolymer, polyamide, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylate, sodium carboxymethyl cellulose, polyvinyl acetate, polyvinylpyrrolidone, polyvinyl ether, polytetrafluoroethylene or polyhexafluoropropylene. In some embodiments, the positive electrode conductor may include at least one of conductive carbon black, acetylene black, Ketjen black, graphene, carbon nanotubes or carbon fibers.

[0060] The material and shape of the separator used in the secondary battery of the present application are not particularly limited, and can be any technology disclosed in the prior art. In some embodiments, the separator includes a polymer or inorganic substance formed of a material that is stable to the electrolyte of the present application.

[0061] In some embodiments, the isolation membrane may include a substrate layer and a surface treatment layer. The substrate layer is a non-woven fabric, a film or a composite film having a porous structure, and the material of the substrate layer is selected from at least one of polyethylene, polypropylene, polyethylene terephthalate and polyimide. Specifically, a polypropylene porous film, a polyethylene porous film, a polypropylene non-woven fabric, a polyethylene non-woven fabric or a polypropylene-polyethylene-polypropylene porous composite film can be selected.

[0062] A surface treatment layer is provided on at least one surface of the substrate layer, and the surface treatment layer can be a polymer layer or an inorganic layer, or a layer formed by a mixed polymer and an inorganic substance. The inorganic layer includes inorganic particles and a binder, and the inorganic particles are selected from at least one of aluminum oxide, silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide and barium sulfate. The binder is selected from at least one of polyvinylidene fluoride, a copolymer of vinylidene fluoride-hexafluoropropylene, polyamide, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylic acid salt, polyvinylpyrrolidone, polyethylene alkoxy, polymethyl methacrylate, polytetrafluoroethylene and polyhexafluoropropylene. The polymer layer contains a polymer, and the material of the polymer is selected from at least one of polyamide, polyacrylonitrile, acrylate polymer, polyacrylic acid, polyacrylic acid salt, polyvinylpyrrolidone, polyethylene alkoxy, polyvinylidene fluoride and poly (vinylidene fluoride-hexafluoropropylene).

[0063] In some embodiments, the coating is located on one surface or two opposite surfaces of the isolation film. In some embodiments, the coating is located on the surface of the surface treatment layer away from the substrate layer.

[0064] In some embodiments, the electrolyte of the secondary battery includes a lithium salt and a non-aqueous solvent. The present application has no particular restrictions on the lithium salt, as long as the purpose of the present application can be achieved. For example, the lithium salt may include, but is not limited to, at least one of LiPF6, LiBF4, LiClO4, LiB(C6H5)4, LiCH3SO3, LiCF3SO3, LiN(SO2CF3)2, LiC(SO2CF3)3, Li2SiF6, lithium bis(oxalate borate) (LiBOB) or lithium difluoroborate. The present application has no particular restrictions on the content of the lithium salt in the electrolyte, as long as the purpose of the present application can be achieved. For example, based on the mass of the electrolyte, the mass percentage of the lithium salt is 5% to 23%. For example, the concentration of the lithium salt in the electrolyte can be 5%, 8%, 12%, 16%, 20%, 23% or a range consisting of any two of the above values.

[0065] In some embodiments, the electrolyte includes 1,3-propane sultone and fluoroethylene carbonate. The electrolyte containing 1,3-propane sultone and fluoroethylene carbonate can cooperate with the coating to stabilize the anode of the secondary battery, reduce the impedance of the secondary battery, and thus improve the thermal stability and cycle performance of the secondary battery.

[0066] In some embodiments, the sum of the percentages of 1,3-propane sultone and fluoroethylene carbonate in the electrolyte to the total mass of the electrolyte is 0.1% to 5%, for example, it can be 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5% as a range consisting of any two of the above values. The sum of the percentages of 1,3-propane sultone and fluoroethylene carbonate is controlled within this range, which helps to reduce impedance and improve the thermal stability and cycle performance of the secondary battery.

[0067] In some embodiments, the secondary battery further comprises a negative electrode plate, the negative electrode plate comprising a negative electrode current collector and a negative electrode material layer disposed on the negative electrode current collector. The negative electrode material layer comprises at least one of natural graphite, artificial graphite or a silicon-based material. In some embodiments, the silicon-based material comprises at least one of silicon, a silicon-oxygen compound, a silicon-carbon compound or a silicon alloy.

[0068] The negative electrode current collector can be at least one of copper foil, nickel foil, stainless steel foil, titanium foil or a carbon-based current collector, or any composite current collector disclosed in the prior art. In some optional embodiments, but not limited to, the current collector is formed by combining the aforementioned conductive foil and a polymer substrate.

[0069] The negative electrode material layer also includes a binder to bind the negative electrode active material particles to facilitate the formation of a film layer, and at the same time, it can also improve the binding force between the negative electrode material layer and the negative electrode current collector. In some embodiments, the binder may include but is not limited to polyvinyl alcohol, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polymers containing ethylene oxide, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene butadiene rubber, acrylic (ester) styrene butadiene rubber, epoxy resin or nylon, etc.

[0070] The negative electrode material layer may also include a conductive material, including but not limited to a carbon-based material, a metal-based material, a conductive polymer, or any combination thereof. In some embodiments, the carbon-based material may include but is not limited to natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, or any combination thereof. In some embodiments, the metal-based material may include but is not limited to metal powder or metal fiber, in some optional embodiments copper, nickel, aluminum or silver. In some embodiments, the conductive polymer may be a polyphenylene derivative.

[0071] The negative electrode material layer may further include a dispersant, the dispersant including at least one of sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, carboxymethyl cellulose, lithium hydroxypropyl carboxymethyl cellulose, sodium hydroxypropyl carboxymethyl cellulose, hydroxypropyl carboxymethyl cellulose, lithium hydroxyethyl carboxymethyl cellulose, sodium hydroxyethyl carboxymethyl cellulose or hydroxyethyl carboxymethyl cellulose.

[0072] In some embodiments, the secondary battery is a lithium-ion battery, but the present application is not limited thereto.

[0073] In some embodiments of the present application, taking lithium-ion batteries as an example, the positive electrode sheet, the isolation membrane, and the negative electrode sheet are wound or stacked in sequence to form an electrode assembly, and then placed in a shell such as an aluminum-plastic film for packaging, and the electrolyte is injected, formed, and packaged to make a lithium-ion battery.

[0074] The embodiment of the present application also provides an electronic device including the above-mentioned secondary battery. The secondary battery is powered by the electronic device, and the secondary battery shows good high temperature storage performance, thermal stability and cycle performance after high temperature storage performance test, high temperature cycle performance test and hot box test. Among them, the electronic device may include but is not limited to a laptop computer, a pen input computer, a mobile computer, an e-book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, an LCD TV, a portable cleaner, a portable CD player, a mini disc, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power bicycle, a bicycle, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera, a large household battery and a lithium ion capacitor, etc.

[0075] The present application is described below by specific examples and comparative examples. Those skilled in the art should understand that the preparation methods described in the present application are only examples, and any other suitable preparation methods are within the scope of the present application.

[0076] Preparation of melamine compounds

[0077] The preparation method of the melamine compound of Example 1-2 to Example 1-14 is: on the basis of the preparation method of the melamine compound of Example 1-1, the amount of the crystal growth factor and the amount of cyanuric acid are adjusted. Example 1-2 to Example 1-7 are to adjust the amount of the crystal growth factor on the basis of Example 1-1, and the amount of the crystal growth factor is in the range of 0.05 to 0.5 parts. Example 1-8 to Example 1-14 are to adjust the amount of cyanuric acid added in the third batch, and the amount of cyanuric acid is in the range of 1.01 to 1.1 parts.

[0078] The preparation method of the melamine compound of Comparative Example 1-1 is as follows: Based on the preparation method of Example 1-1, the amount of the crystal growth factor used is 0.6 parts.

[0079] The preparation method of the melamine compound of Comparative Example 1-2 is as follows:

[0080] Based on the preparation method of Example 1-1, the amount of crystal growth factor used is 0 parts.

[0081] The preparation methods of the melamine compounds of Comparative Examples 1-3 are as follows:

[0082] Based on the preparation method of Example 1-1, the amount of crystal growth factor used is 0.03 parts.

[0083] Comparative Examples 1-4 use aluminum oxide instead of the melamine compound.

[0084] Example 1-1

[0085] Preparation of melamine compounds

[0086] Put 5 parts of 1,3,5-triazine-2,4,6-triamine compound into a 5-liter stirrer equipped with a mechanical stirrer, a thermometer and a cooler, add 20 parts of water, start the stirrer and heat at 90°C, stir at 300 rpm for 2 hours to obtain a 1,3,5-triazine-2,4,6-triamine solution. Use sodium hydroxide to adjust the pH value of the 1,3,5-triazine-2,4,6-triamine solution to 9-10. Then add 0.1 parts of crystal growth factor (referring to melamine cyanurate seed crystals with a particle size of 1-40 nanometers) to the 1,3,5-triazine-2,4,6-triamine solution.

[0087] The mixture was stirred at 500 rpm for 10 min. Cyanuric acid was then added to the 1,3,5-triazine-2,4,6-triamine solution in three batches, with the order of 2 parts of cyanuric acid, 2 parts of cyanuric acid and 1.1 parts of cyanuric acid. The temperature was kept at 110°C and the mixture was stirred for 2 h to obtain a viscous white paste. The mixture was then vacuum filtered, washed and dried, and the product was subjected to ultrafine grinding to obtain melamine cyanurate.

[0088] Preparation of lithium-ion batteries

[0089] (1) Preparation of positive electrode sheet

[0090] The positive electrode active material lithium cobalt oxide, the conductive agent conductive carbon black, and the binder polyvinylidene fluoride are added to N-methylpyrrolidone in a weight ratio of 96:2.5:1.5, and stirred evenly to form a positive electrode slurry. The positive electrode slurry is evenly coated on one side of the positive electrode collector aluminum foil, dried, and then the above steps are repeated on the other side of the aluminum foil to obtain a positive electrode sheet coated with a positive electrode active layer on both sides, which is then cold pressed and cut to obtain a positive electrode sheet.

[0091] (2) Preparation of negative electrode sheet

[0092] The negative electrode active material artificial graphite, the dispersant sodium carboxymethyl cellulose and the binder styrene-butadiene rubber are added to deionized water in a weight ratio of 96:2:2, and stirred evenly to form a negative electrode slurry. The negative electrode slurry is evenly coated on one side of the negative electrode collector copper foil, dried, and then the above steps are repeated on the other side of the copper foil to obtain a negative electrode sheet coated with a negative electrode active layer on both sides, which is then cold pressed and cut to obtain a negative electrode sheet.

[0093] (3) Preparation of composite isolation membrane

[0094] A polyethylene porous membrane with a thickness of 5 μm and a porosity of 55% was selected as the substrate layer of the composite isolation membrane.

[0095] The prepared melamine cyanurate was taken, and the residual amount of melamine monomer W1 in the melamine cyanurate was measured to be 0, the residual amount of cyanurate monomer W2 was 0.1, and the pH of its aqueous solution was measured to be 5.5. The residual amount of melamine monomer W1, the residual amount of cyanurate monomer W2 in melamine cyanurate and the pH of its aqueous solution are affected by the ratio of 1,3,5-triazine-2,4,6-triamine compound and cyanuric acid. By adjusting the ratio of melamine monomer and cyanuric acid, different residual amounts of melamine monomer W1, residual amounts of cyanurate monomer W2 and pH of its aqueous solution can be obtained.

[0096] In a dispersion tank, melamine cyanurate and styrene-butadiene rubber binder were added in a mass ratio of 93 parts:7 parts, and then 400 parts of deionized water were added, and the mixture was dispersed and mixed evenly to obtain a coating slurry. The coating slurry was coated on one surface of the substrate layer by gravure roller transfer coating, and dried in an oven. The coating thickness of the coating composition on the substrate layer was 2 μm, and the composite isolation film was rolled up.

[0097] (4) Preparation of electrolyte

[0098] In a glove box filled with argon, first add 3.5% of the total mass of the electrolyte, succinonitrile and 85% of the chain carbonate (the mass ratio of EP:EMC:DEC:PP is 15:20:20:45), and then weigh 0.15% of the total mass of the electrolyte, 1,3-propane sultone and fluoroethylene carbonate, and the rest are lithium salt LiPF6.

[0099] (5) Assembly

[0100] The prepared positive electrode sheet, composite isolation membrane, and negative electrode sheet are stacked in order so that the composite isolation membrane is between the positive electrode sheet and the negative electrode sheet to obtain a stacked electrode assembly. After welding the electrode ears, the electrode assembly is placed in an aluminum-plastic film packaging bag, heat-sealed on all sides, leaving a liquid injection port, and the above-mentioned electrolyte is injected. After vacuum packaging, standing, formation, degassing and other processes, a lithium-ion battery is obtained.

[0101] Coating composition characterization tests

[0102] (1) K1, K2, K3 values

[0103] An equal amount of the melamine compound of each embodiment and comparative example was taken and scanned in an X-ray powder diffractometer (in-situ X-ray powder diffractometer DB Advance 250) to obtain an X-ray diffraction pattern, wherein K1 is the peak intensity of the crystal plane of melamine compound 110, K2 is the peak intensity of the crystal plane of melamine compound 200, and K3 is the peak intensity of the crystal plane of melamine compound 202. The values ​​of K1, K2, and K3 were read from the X-ray diffraction pattern, and the values ​​of K1 / K2 and K2 / K3 were calculated.

[0104] (2) The residual amount of melamine monomer W1 and the residual amount of cyanuric acid monomer W2 in the melamine compound

[0105] The precipitation method is used for testing. A certain mass M1 melamine compound is dispersed in water, filtered to obtain a dissolved solution, and cyanuric acid solution is added. The solution is heated to react to generate an insoluble melamine precipitate. The precipitate is filtered to obtain the precipitate, dried and weighed to obtain M2. W1 = (M1-M2) / M1×100%.

[0106] The precipitation method is used for testing. A certain mass M1 melamine compound is dispersed in water, filtered to obtain a dissolved solution, and melamine solution is added. The solution is heated to react to generate an insoluble melamine precipitate. The precipitate is filtered to obtain a precipitate, dried and weighed to obtain M3. W2 = (M1-M3) / M1×100%.

[0107] (3) pH of aqueous solution of melamine compound

[0108] In the aqueous solution of the melamine compound, water accounts for 90 wt % and the melamine compound accounts for 10 wt %. The pH value of the aqueous solution of the melamine compound is measured by a pH meter.

[0109] (4) Primary particle size D50, primary particle size D90

[0110] Take 1g of melamine compound sample and disperse it in 40g of aqueous solution, add 1-2 drops of 0.5wt% sodium hexametaphosphate dispersant, perform ultrasound for 10 minutes, and then place it in a laser particle size analyzer to test the primary particle size D50 and primary particle size D90.

[0111] Coating performance test

[0112] (1) Resistance to heat shrinkage

[0113] The composite isolation film was cut into square size and accurately measured using a microscope. The length of the composite isolation film in the MD (longitudinal) direction was A0, and the length of the membrane in the TD (transverse) direction was B0, where the lengths of A0 and B0 were both 30 mm. The composite isolation film was placed in a 130°C constant temperature box for 1 hour. The length A1 and width B1 of the membrane were measured using a microscope, and the heat shrinkage resistance of the composite isolation film was obtained according to the following formula.

[0114] Heat shrinkage resistance = (A1 / A0+B1 / B0) / 2*100%.

[0115] (2) Adhesion test

[0116] The fully charged lithium-ion battery was disassembled, and the composite structure of coating plus base film or coating plus positive electrode was taken out and cut into strips with a length of 5 cm and a width of 15 mm. The tensile force was tested in a universal experimental tensile testing machine using a 180° method. The tensile force of 3 strips was tested in each set of tests, and the average of the three test data was then taken.

[0117] Lithium-ion battery performance test

[0118] (1) Impedance

[0119] The lithium-ion battery was placed in a 25°C constant temperature box, left to stand for 10 minutes, charged at a constant current rate of 1C to 4.5V, charged at a constant voltage rate of 0.05C at 4.5V, left to stand for 10 minutes, and the DC impedance of the lithium-ion battery in the fully charged state was measured.

[0120] (2) Thickness expansion rate at 85℃

[0121] The lithium-ion battery was charged at 25°C. After being charged to 4.5V, the thickness of the lithium-ion battery was measured using a panel pressure gap (PPG) thickness gauge. The thickness of the lithium-ion battery at this time was defined as the initial thickness H0 of the lithium-ion battery. The lithium-ion battery was then stored in a constant temperature box at 85°C for 24 hours. The thickness of the lithium-ion battery was measured using the same method. The thickness of the lithium-ion battery after storage was defined as H1.

[0122] 85℃ thickness expansion ratio = (H1-H0) / H0×100%.

[0123] The lower the thickness expansion rate at 85°C, the better the high-temperature storage performance of the battery.

[0124] (3) Hot box pass rate test

[0125] The lithium-ion batteries in the embodiments and comparative examples were charged at room temperature at a constant current of 1C rate to a full charge voltage of 4.5V, and then continued to be charged at a constant voltage of 4.5V to a cut-off current of 0.05C to fully charge the batteries. The appearance was checked to ensure that the lithium-ion batteries were in a normal usable state. The fully charged lithium-ion batteries were placed in an oven and heated at a rate of 5°C / min until the specified hot box test temperature was reached. The temperature was kept constant for one hour, and the state of the lithium-ion batteries was observed during the process.

[0126] Judgment standard: The battery does not catch fire or explode, that is, the battery passes the test temperature.

[0127] The test temperature is increased by 1°C, and the lithium-ion battery is re-obtained and the above test is repeated until the lithium-ion battery fails to pass the test temperature. The highest passable hot box test temperature of the battery in a fully charged state is obtained. The higher the passable hot box test temperature, the better the thermal stability of the battery.

[0128] (4) 45℃ cycle capacity retention rate

[0129] First, in an environment of 45°C, the first charge and discharge were performed, first using a 1C current for constant current charging, charging to 4.5V, then constant voltage charging to a current of 0.05C, and then constant current discharge at a current of 0.5C to 3.0V. Repeat the above charge and discharge cycles, and record the discharge capacity of the 3rd cycle and the discharge capacity of the 400th cycle.

[0130] 45° C. cycle capacity retention rate=(discharge capacity at the 400th cycle / discharge capacity at the 3rd cycle)×100%.

[0131] The higher the 45°C cycle capacity retention rate is, the better the cycle performance of the battery is.

[0132] Test results:

[0133] Figure 1 The X-ray diffraction pattern of melamine cyanurate provided in Examples 1-3 is given by Figure 1 It can be concluded that the K1 value of the melamine cyanurate obtained in Examples 1-3 is 19700, the K2 value is 7000, the K3 value is 30500, and there is a low peak K1-D at the 110 crystal plane. The 2θ diffraction angle of the low peak K1-D is at 10.5°, the 2θ diffraction angle of the peak corresponding to K1 is at 10.9°, the 2θ diffraction angle of the peak corresponding to K2 is at 11.8°, and the 2θ diffraction angle of the peak corresponding to K3 is at 28.0°.

[0134] The X-ray diffraction patterns of the melamine compounds of the other embodiments are similar to those of Figure 1 The 2θ diffraction angles of the peaks corresponding to K1 are all at 10.9°, the 2θ diffraction angles of the peaks corresponding to K2 are all at 11.8°, and the 2θ diffraction angles of the peaks corresponding to K3 are all at 28.0°. There is also a K1-D peak on the 110 crystal plane, and the peak height of K1-D is lower than that of K1. The peak shape of K1-D is lattice distorted, and the 2θ diffraction angle peaks of K1-D are all at 10.5°.

[0135] Figure 2 The X-ray diffraction pattern of melamine cyanurate provided in Comparative Example 1-2. Figure 2It can be seen that the K1 value of the melamine cyanurate of Comparative Example 1-2 is 49000, the K2 value is 30000, the K3 value is 37500, and its X-ray diffraction pattern has no K1-D peak at the 110 crystal plane.

[0136] Examples 1-3

[0137] The preparation method of Example 1-3 is different from that of Example 1-1 only in that in the preparation method of the melamine compound of Example 1-3, the amount of the crystal growth factor used is 0.08 parts, and the rest is the same as that of Example 1-1.

[0138] Embodiment 1-2, Embodiment 1-4 to Embodiment 1-7

[0139] The amount of the crystal growth factor is adjusted to adjust the K1, K2, K3, D50 and D90 of the corresponding melamine compound to obtain the relevant parameters in Table 1 and Table 2. The rest is the same as in Example 1-3.

[0140] Comparative Example 1-1 to Comparative Example 1-3

[0141] The amount of the crystal growth factor is adjusted to adjust the K1, K2, K3, D50 and D90 of the corresponding melamine compound to obtain the relevant parameters in Table 1 and Table 2. The rest is the same as in Example 1-3.

[0142] Comparative Examples 1-4

[0143] The melamine compound in Example 1-1 was replaced by aluminum oxide, and the rest was the same as Example 1-1.

[0144] Example 1-8 to Example 1-14

[0145] The amount of cyanuric acid used was adjusted to adjust the corresponding residual amount of melamine monomer W1, the residual amount of cyanuric acid monomer W2 and the pH of the aqueous solution of the melamine compound to obtain the relevant parameters in Table 3. The rest is the same as in Example 1-3.

[0146] Example 1-15 to Example 1-22

[0147] The coating thickness of the coating composition on the substrate layer was adjusted to obtain the relevant parameters in Table 4, and the rest was the same as in Example 1-3.

[0148] In Examples 1-23 to 1-26, the mass ratio of the melamine compound to the adhesive was adjusted to obtain the relevant parameters in Table 5, and the rest was the same as in Example 1-3.

[0149] Example 2-1

[0150] The difference between Example 2-1 and Example 1-3 is that the coating composition of Example 2-1 is coated on one surface of the positive electrode plate, and in the electrolyte of Example 2-1, the total percentage of 1,3-propane sultone and fluoroethylene carbonate in the electrolyte is 0.1wt%.

[0151] Example 2-2 to Example 2-8

[0152] The sum of the percentages of 1,3-propane sultone and fluoroethylene carbonate in the electrolyte was adjusted to obtain the relevant parameters in Table 6, and the rest were the same as in Example 1-3.

[0153] Comparative Example 2-1

[0154] The only difference between Comparative Example 2-1 and Example 1-3 is that no coating composition is coated on the substrate layer of Comparative Example 2-1, and the rest is the same as Example 1-3.

[0155] Table 1

[0156]

[0157]

[0158] Table 2

[0159]

[0160] In the above Table 1 and Table 2, compared with Comparative Examples 1-1 to 1-3, in Examples 1-1 to 1-7, when the K1 / K2, K2 / K3, D50 and D90 values ​​of the melamine compound are within a suitable range, the heat shrinkage resistance of the separator is improved, the impedance of the lithium-ion battery is reduced, and the thickness expansion rate of the lithium-ion battery at a high temperature of 85°C is reduced, the hot box test passing temperature and the 45°C cycle capacity retention rate are improved, and therefore, the high temperature storage performance, thermal stability and high temperature cycle performance of the lithium-ion battery are improved. In particular, when 1.9≤K1 / K2≤2.7 and / or 0.2≤K2 / K3≤0.5, the impedance of the lithium-ion battery is further reduced, and the heat shrinkage resistance of the separator of the lithium-ion battery is improved. Thus, the high temperature storage performance, thermal stability and cycle performance of the lithium-ion battery are further improved.

[0161] Table 3

[0162]

[0163] In the above Table 3, in Examples 1-3 and 1-8 to 1-14, when the residual amount of melamine monomer W1, the residual amount of cyanuric acid monomer W2 and / or the pH of the aqueous solution of melamine compound are within a suitable range, it is beneficial to improve the adhesion of the coating and the 45°C cycle capacity retention rate.

[0164] Table 4

[0165]

[0166]

[0167] In the above Table 4, in Examples 1-3 and Examples 1-15 to 1-22, the thickness of the coating is adjusted. When the thickness of the coating is within a suitable range, it is beneficial to improve the hot box test passing temperature and 45°C cycle capacity retention rate of the lithium ion battery, that is, it is beneficial to improve the thermal stability and cycle stability of the lithium ion battery.

[0168] Table 5

[0169]

[0170] In the above Table 5, in Examples 1-3 and Examples 1-22 to 1-26, the mass ratio of the melamine compound to the binder is adjusted. When the mass ratio of the melamine compound to the binder is within a suitable range, it is beneficial to improve the adhesion of the coating, reduce the impedance of the lithium ion battery, and enhance the thermal stability and cycle performance of the lithium ion battery.

[0171] Table 6

[0172]

[0173] In the above Table 6, in Examples 1-3 and 2-1 to 2-8, adjusting the sum of the percentages of 1,3-propane sultone and fluoroethylene carbonate is beneficial to reducing the impedance of the lithium ion battery and improving the thermal stability and cycle stability of the lithium ion battery.

[0174] Compared with Example 2-3, Comparative Example 2-1 shows that the lithium-ion battery after the surface of the isolation membrane is coated with the coating composition has lower impedance, better thermal stability and better cycle stability.

[0175] The above implementation modes are only used to illustrate the technical solutions of the present application and are not intended to limit the present application. Although the present application is described in detail with reference to the above implementation modes, a person skilled in the art should understand that the technical solutions of the present application may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present application.

Claims

1. A coating composition, characterized in that Comprising a melamine compound and a binder, The melamine compound includes melamine cyanurate, The melamine compound satisfies the following relationship at the same time: 1.8≤K1 / K2≤3.0, 0.18≤K2 / K3≤0.5, K3≥K1≥K2, Among them, in the X-ray diffraction pattern of the melamine compound, K1 is the highest peak intensity of the crystal plane 110 of the melamine compound, K2 is the peak intensity of the crystal plane 200 of the melamine compound, and K3 is the peak intensity of the crystal plane 202 of the melamine compound.

2. The coating composition according to claim 1, characterized in that The melamine compound satisfies at least one of the following conditions: (1) 1.9 ≤ K1 / K2 ≤ 2.7; (2) 0.2≤K2 / K3≤0.5; (3) K1-D is the lowest peak of the crystal plane of the melamine compound 110, and the peak shape of K1-D undergoes lattice distortion. The 2θ diffraction angle of K1-D is at 10.5°±0.5°, the 2θ diffraction angle of the peak corresponding to K1 is at 10.9°±0.5°, the 2θ diffraction angle of the peak corresponding to K2 is at 11.8°±0.5°, and the 2θ diffraction angle of the peak corresponding to K3 is at 28.0°±0.5°.

3. The coating composition according to claim 1, characterized in that The residual amount W1 of melamine monomer in the melamine compound is ≤1wt%, the residual amount W2 of cyanuric acid monomer in the melamine compound is ≤1wt%, and the residual amount W1 of melamine monomer and the residual amount W2 of cyanuric acid monomer in the melamine compound are not 0 at the same time.

4. The coating composition according to claim 1, characterized in that The pH value of the aqueous solution of the melamine compound is 5≤PH≤6.5, wherein the proportion of water in the aqueous solution of the melamine compound is 90wt%, and the proportion of the melamine compound is 10wt%.

5. The coating composition according to claim 1, characterized in that The primary particle size D50 of the melamine compound is 0.3 to 1.5 μm.

6. The coating composition according to claim 1, characterized in that The primary particle size D50 of the melamine compound is 0.4 to 1.0 μm.

7. The coating composition according to claim 1, characterized in that The primary particle size D90 of the melamine compound is 0.6 to 3.0 μm.

8. The coating composition according to any one of claims 1 to 7, characterized in that The mass ratio of the melamine compound to the binder is (90-95):(5-10).

9. A coating, characterized in that: The coating comprises the coating composition according to any one of claims 1 to 8.

10. The coating according to claim 9, characterized in that The thickness of the coating is 0.8-3.5 μm.

11. The coating according to claim 10, characterized in that The coating has a thickness of 1.0 to 3.0 μm.

12. A secondary battery, characterized in that: The secondary battery comprises the coating according to claim 9, a positive electrode sheet, a separator and an electrolyte, wherein the coating is disposed on at least one surface of the positive electrode sheet or the separator.

13. The secondary battery according to claim 12, characterized in that: The electrolyte contains 1,3-propane sultone and fluoroethylene carbonate.

14. The secondary battery according to claim 13, characterized in that: The sum of the percentages of 1,3-propane sultone and fluoroethylene carbonate in the electrolyte to the total mass of the electrolyte is 0.1% to 5%.

15. An electronic device comprising the secondary battery according to any one of claims 12 to 14.

Citation Information

Cited By

  • Diaphragm and battery

    CN121261044A

  • A separator and a battery

    CN121261044B

  • Coating, coating composition, secondary battery and electronic device

    WO2026086405A1